PRODUCTION OF BLENDED YARN FROM LOCAL WOOL AND POLYESTER FIBERS USING THE “SIRO” SPINNING METHOD - S. N. Yarashov; V. T. Isaqulov; M. V. To‘laganova; A. M. Sarsenbaeva (Journal Park Publishing, 2025)
The article describes the process of preparing raw materials for the production of blended yarn using the “Siro” method from local wool and polyester fibers. In this case, the dependence of the product linear density on the drawing length, the number of twists, and the machine’s adjustment parameters has been established. The physical and mechanical properties of the” Siro” blended yarn, numbered Ne=20, obtained as a result of the experiment, were studied.
Keywords: Statistical, analys, local, wool, fibers, country, physical, karakul, mechanical, republic, sheep, diameter, deviation, mic, variation.